(untitled) (Revista de Estudos Orientais, 2016)
In this article, the reading of the Bible in Hebrew is discussed as well the difficulties of translating the Leitworter, "those series of similar or formally linked words "which Rozenzweig tokk as a kind of cue to understand the meaning of the text.